Chilean transition and transitional justice: Critical analysis - Nash Rojas, Claudio (2016)
This paper aims to review the model of transitional justice applied in Chile as part of a growing critical assessment has been formulating the Inter-American Court of Human Rights in its jurisprudence about the way that the states resolve the issues of truth, justice, reparation of victims and institutional design in processes of democratic transition and democratic consolidation. We will try to show that the conflict is a consequence of the characteristics of gross and systematic violations and political limits imposed transitional processes characteristics. The way this tension is resolved is what sets a model of transitional justice that fulfill or not the international standards on human rights.